2011
DOI: 10.1002/ird.541
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of a distributed irrigation water management model using remotely sensed evapotranspiration rates and groundwater heads

Abstract: Parameters of the distributed irrigation water management model FRAME are determined by an inverse method using evapotranspiration (ET) rates estimated from the SEBAL remote sensing procedure and in situ measurement of groundwater heads. The model simulates canal and on-farm water management as well as regional groundwater flow. The calibration is achieved in two phases. The data on ET were introduced with the primary intent of improving predictions of ET through better estimated soil hydraulic parameters. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Then, parameter sensitivity analysis was applied, and the model was systematically calibrated using the observed river discharge and the actual ET (ET a ) for the mountainous area and the plain area, respectively. Especially, RS techniques can provide the data information with a high spatial observational resolution over large areas (McCabe and Wood, ), which have been successfully applied in parameterization of hydrological models in other watersheds (Immerzeel and Droogers, ; Jhorar et al ., ). In this study, we attempted to use the observed ET a data derived from RS for model calibration in the plain area as well.…”
Section: Introductionmentioning
confidence: 97%
“…Then, parameter sensitivity analysis was applied, and the model was systematically calibrated using the observed river discharge and the actual ET (ET a ) for the mountainous area and the plain area, respectively. Especially, RS techniques can provide the data information with a high spatial observational resolution over large areas (McCabe and Wood, ), which have been successfully applied in parameterization of hydrological models in other watersheds (Immerzeel and Droogers, ; Jhorar et al ., ). In this study, we attempted to use the observed ET a data derived from RS for model calibration in the plain area as well.…”
Section: Introductionmentioning
confidence: 97%
“…Except for Jhorar et al (2011), Winsemius et al (2008 and Rientjes et al (2013), this is rarely done because water managers and hydrologists do not accept ET layers as being sufficiently accurate. This new analysis proves that the science of remote sensing in the last 13 years has advanced and that mapping of ET has become more reliable.…”
Section: Accuracy Of Spatial Evapotranspiration Datamentioning
confidence: 99%
“…Immerzeel and Droogers (2008), for example, applied the SWAT (Soil and Water Assessment Tool) model to the Upper Bhima catchment in southern India (45 678 km 2 ) and adjusted the monthly evapotranspiration for each sub-basin to the ET a -estimates of the SEBAL (Surface Energy Balance Algorithm for Land) algorithm (Bastiaanssen et al, 1998a,b) applied to thermal imagery from the Moderate Resolution Imaging Spectroradiometer (MODIS) satellite. Singh et al (2010) and Jhorar et al (2011) used remotely sensed ET rates for improving agro-hydrological models on irrigated plots.…”
Section: Hydrological Modelling and Remote Sensingmentioning
confidence: 99%